Antitumor activity of tamoxifen loaded solid lipid nanoparticles on induced mammary tumor gland in Sprague-Dawley rats - Abbasalipourkabirreh, Roghayeh; Salehzadeh, Aref; Abdullah, Rasedee (Academic Journals, 2010)
An in vivo study was conducted to determine the effect of tamoxifen-loaded solid lipid nanoparticle on LA7 cell-induced rat mammary tumor. After the first tumors appearance, the thirty rats were divided into five groups. Group I served as normal control animal. The other four groups were mammary gland tumor-bearing animals treated with soy oil (Group II), tamoxifen (TAM) dissolved in soy oil (Group III), tamoxifen-loaded solid lipid nanoparticle (Group IV) and solid lipid nanoparticle (SLN) (Group V) dispersed in soy oil. The effect of TAM-loaded SLN in the reduction of tumor size was greater than that of free TAM. The transmission electron microscope analysis showed apoptosis in TAM-loaded SLN and free TAM treatment groups. After treatment, the rats treated with TAM-loaded SLN showed decreases in concentration of serum enzymes. In conclusion, the study suggests that TAM-loaded SLN is very effective for treatment of rat mammary gland tumors and breast cancers.